2012
DOI: 10.1590/s0004-27302012000100006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quality of life in severely obese patients after bariatric surgery carried out in the public healthcare system

Abstract: Objectives: To assess QoL of obese patients in the Brazilian public healthcare system, before and after bariatric surgery, and to determine the appropriateness of the Moorehead-Ardelt Questionnaire II (M-A-QoLQII) compared with the Short-Form Health Survey (SF-36). Subjects and methods: Forty-one severe obese patients in a waiting-list, and 84 patients who underwent bariatric surgery were included. Correlations were tested and reliability determined by the Cronbach's coefficient. Results: BMI differed between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
1
11
0
8
Order By: Relevance
“…A study that assessed QoL of patients before and after bariatric surgery in the Brazilian public health system showed that after surgery, 82.2% of patients considered their quality of life as being good or very good, which contrasted the 40% of patients who expressed the same opinion during the preoperative period (15) . These fi ndings confi rm that an improved quality of life is fundamental for the success of bariatric surgery, which often transforms the lives of obese individuals (16) .…”
Section: Discussionmentioning
confidence: 99%
“…A study that assessed QoL of patients before and after bariatric surgery in the Brazilian public health system showed that after surgery, 82.2% of patients considered their quality of life as being good or very good, which contrasted the 40% of patients who expressed the same opinion during the preoperative period (15) . These fi ndings confi rm that an improved quality of life is fundamental for the success of bariatric surgery, which often transforms the lives of obese individuals (16) .…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, the availability of bariatric surgery on the SUS still falls below demand: the length of time spent on the waiting list for this type of operation can vary between 1 and 4 years. 13 Whereas more than 100,000 procedures per annum are performed by private and supplementary health services, SUS does not achieve so much as 10% of this total.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, with the use of generic instruments such as SF-36, the HRQoL is assessed both, at pre and post-operative time, by each of eight domains (limitations in physical activities, social activities usual role activities, bodily pain, general mental health, vitality, and general health perception) [36], and it is possible to evaluate the HRQoL both at the time of the pre-operative and post-operative [37]. However, since it is a generic healthrelated HRQoL measurement, in contrast with BAROS which is a disease specific instrument developed to study samples of obese patients [38], SF-36 may not capture all the changes that occur with the obese population who undergo bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%